Characterizing Breast Deformities After Massive Weight Loss: Utilizing the Pittsburgh Rating Scale to Examine Factors Affecting Severity Score and Surgical Decision Making in a Retrospective Series. Issue 3 (March 2018) - Pang, John Henry; Coombs, Demetrius M.; James, Isaac; Fishman, Jordan; Rubin, J. Peter; Gusenoff, Jeffrey A.
Abstract : Background and Objectives: Massive weight loss (MWL) can result in variable contour deformities of the breasts. The Pittsburgh Rating Scale (PRS) was designed to describe the multitude of deformities after MWL and recommends operations to consider for surgical improvement. We present the first comprehensive description of breast deformities in a large sample of MWL patients, examine factors affecting the severity of deformities, and report the correlation between PRS score and surgical decision making. Methods: A retrospective review of all MWL patients presenting for breast surgery at our institution's Life After Weight Loss program from 2004 to 2015 was performed. Information including demographics, body mass indices (BMIs), method of weight loss, and type of surgical intervention was collected. Preoperative breast photographs were blinded and scored according to the PRS. Results: A total of 204 MWL patients were identified; 26% (53) scored 1, 34% (69) scored 2, and 40% (82) scored 3 on the PRS. Greater deformities were seen after weight loss from bariatric surgery versus diet and exercise alone ( P = 0.031), in mastopexy versus augmentation/mastopexy ( P = 0.001), and in breast reduction versus augmentation/mastopexy patients ( P > 0.0001). Patients who underwent reduction mammaplasty had the greatest maximum BMI compared with other procedures ( P = 0.016). The PRS scores were positively correlated to maximum BMI ( P < 0.001), delta BMI ( P < 0.001), and current BMI ( P < 0.001). Conclusions: Massive weight loss patients have variable, and often severe, breast deformities, and the PRS remains a valuable classification tool. Severity scores correlate with BMI, procedure, and weight loss mechanism. Similar scores between mastopexy-only and reduction mammaplasty patients may reflect a composite of personal cosmetic expectations and cost. The PRS scale should also be expanded to include breast reduction as a surgical remedy for PRS grade 3 breast deformities. Understanding breast deformities in this unique population has applications in both preoperative planning and surgical expectations for this unique patient population.